Health Education (Demonstration) Quadriceps Setting For Preventing Knee Pain in The Elderly Group Of The Foundation’s Foundation Area Princess Of Love - Anastasia Putu Martha Anggarani; Raditya Kurniawan Djoar; Elsa Davina Zefanya; Serti Dewi Wijaya (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
As we get older, changes arise as a result of the aging process, one of which is changes in musculoskeletal function, namely changes in joint function. One example of a change in joint function due to aging is knee osteoarthritis which occurs after 60 years of age. The purpose of carrying out this activity in the elderly community in the area of ??Putri Kasih Tambakmayor Foundation, Surabaya is so that the elderly in this community are able to do Quadriceps Settings and be able to understand the purpose of doing Quadriceps Settings. The methods used in this activity are lectures and demonstrations using media in the form of mics, speakers and flipcharts. The health education carried out begins with giving a questionnaire to the elderly in the community. After the questionnaire and health education have been completed, the next step is a question and answer session which will be followed by a questionnaire at the end of the activity. After all stages have been completed, the presenter collects data from the questionnaire that has been carried out at the beginning and end of the event. Based on the activities that have been carried out, the results obtained were that the elderly who had good knowledge before getting health education were 31%, while after the health education, the elderly who had good knowledge increased to 71%. This shows that a person's knowledge can be increased through health education with demonstration methods the presenter collects data from the questionnaire that has been carried out at the beginning and end of the event. Based on the activities that have been carried out, the results obtained were that the elderly who had good knowledge before getting health education were 31%, while after the health education, the elderly who had good knowledge increased to 71%. This shows that a person's knowledge can be increased through health education with demonstration methods the presenter collects data from the questionnaire that has been carried out at the beginning and end of the event. Based on the activities that have been carried out, the results obtained were that the elderly who had good knowledge before getting health education were 31%, while after the health education, the elderly who had good knowledge increased to 71%. This shows that a person's knowledge can be increased through health education with demonstration methods